PENGARUH PROFITABILITAS (ROA), LEVERAGE (LTDER) DAN INTENSITAS AKTIVA TETAP TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Ali Jamaludin (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of Profitability (ROA), Leverage (LTDER), and Intensity of Fixed Assets Against Tax Avoidance. The population in this study were all food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI) in 2015-2017, namely 18 companies. Data collection using purposive sampling method and based on predetermined criteria, the number of samples obtained were 12 food and beverage sub-sector manufacturing companies listed on the Stock Exchange during the 2015-2017 period. The data analysis method used is the panel data regression analysis method. The results showed that: 1) Profitability (Return On Assets) had a negative and not significant effect on Tax Avoidance, 2) Leverage (Long Term Debt to Equity Ratio) had no effect on Tax Avoidance, 3) CapitL Intensity had no effect on Tax Avoidance.